Cytogenetic analysis in Thoracocharax stellatus (Kner, 1858) (Characiformes, Gasteropelecidae) from Paraguay river basin, Mato Grosso, Brazil - da Silva, Edson Lourenço [UNESP]; de Borba, Rafael Splendore [UNESP]; Centofante, Liano; Miyazawa, Carlos Suetoshi; Parise-Maltempi, Patrícia Pasquali [UNESP] (My University, 2012)
Thoracocharax stellatus (Characiformes, Gasteropelecidae) is a small Neotropical species of fish, widely distributed in several rivers of South America. Evidence for karyotype heteromorphysm in populations from different geographical regions has been reported for this species. In this way, populations of T. stellatus from the Paraguay River basin were cytogenetically characterized and the results were compared with other studies performed in the same species but from different basins. The results showed a diploid number of 2n = 54 for T. stellatus, with chromosomes arranged in 6 metacentric (m), 6 submetacentric (sm), 2 subtelocentric (st) and 40 acrocentric (a), for both sexes, with a simple Nucleolus Organiser Region (NOR) system reported by the techniques of silver nitrate impregnation and fluorescent in situ hybridisation (FISH) using 18S rDNA sequences as probe. The distribution of constitutive heterochromatin, observed by the C-band technique and Chromomycin A3 staining showed great similarity among the analyzed populations and consists mainly of discrete blocks in the pericentromeric and telomeric regions of most chromosomes. The presence of female heterogamety was alsoobserved indicating a ZZ/ZW system with W chromosome almost totally heterochromatic. The results also show cytogenetic diversity of the group and are useful to understand the mechanisms of karyotype evolution of the family. © Edson Lourenço da Silva et al.
Keywords: 18S rDNA; Ag-NOR; C-band; FISH; Thoracocharax stellatus